2015
DOI: 10.1002/cbin.10421
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural maturation of human bone marrow mesenchymal stem cells‐derived cardiomyocytes under alternative induction of 5‐azacytidine

Abstract: Adult cardiomyocytes lack the ability to proliferate and are unable to repair damaged heart tissue, therefore differentiation of stem cells to cardiomyocytes represents an exceptional opportunity to study cardiomyocytes in vitro and potentially provides a valuable source for replacing damaged tissue. However, characteristic maturity of the in vitro differentiated cardiomyocytes and methods to achieve it are yet to be optimized. In this study, differentiation of human bone marrow-mesenchymal stem cells (hBM-MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…These results fit well with previous in vitro cytocompatibility tests carried out on PU fibers (Kuo et al, 2014). It was previously reported that MSCs can differentiate into cardiomyocyte-like cells after 5-azacytidine treatment (Antonitsis et al, 2007;Zhang et al, 2009;Li et al, 2013; Supokawej et al, 2013;Wu et al, 2013;Piryaei et al, 2015). Nartprayut et al showed the ability of perinatally derived MSC differentiation into cardiomyocyte-like cells (after 5-azacytidine treatment) that expressed the cardiac-specific genes Nkx2.5, α-cardiac actin, and cardiac troponin T .…”
Section: Discussionsupporting
confidence: 88%
“…These results fit well with previous in vitro cytocompatibility tests carried out on PU fibers (Kuo et al, 2014). It was previously reported that MSCs can differentiate into cardiomyocyte-like cells after 5-azacytidine treatment (Antonitsis et al, 2007;Zhang et al, 2009;Li et al, 2013; Supokawej et al, 2013;Wu et al, 2013;Piryaei et al, 2015). Nartprayut et al showed the ability of perinatally derived MSC differentiation into cardiomyocyte-like cells (after 5-azacytidine treatment) that expressed the cardiac-specific genes Nkx2.5, α-cardiac actin, and cardiac troponin T .…”
Section: Discussionsupporting
confidence: 88%
“…Beating cardiomyogenic cells were formed from murine bone marrow stromal cells after 2 weeks of culture, following treatment with 3 μM aza for 24 hr (Makino et al, 1999). On the other hand, continuous exposure to aza resulted in greater cell death, while single exposure to aza caused relatively smaller fraction of MSCs to differentiate into immature phenotype (Piryaei et al, 2015). On the other hand, continuous exposure to aza resulted in greater cell death, while single exposure to aza caused relatively smaller fraction of MSCs to differentiate into immature phenotype (Piryaei et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Several pre‐clinical and clinical studies have evaluated some cell types for cardiac regeneration, including skeletal myoblasts, mesenchymal stem cells (bone marrow‐derived and adipose‐derived), embryonic stem cells, and cardiac stem cells. The majority of these cell types are produced preclinically and are safe and effective in clinical practice; however, it has been shown that cardiac stem cells or cardiopoietic stem cells are more effective than other cell types and surgeons are thus keen to use lineage‐specified cells derived from the heart for ideal treatment of heart diseases [Ahmadi et al, ; Piryaei et al, ]. A summary of the findings of studies used in this review is shown in Table .…”
Section: Cell Therapymentioning
confidence: 99%